The kinematic analysis of the lumbar, lumbosacral, and hip joints in the dolphin kick swimming - Obayashi, H.; Urabe, Y.; Ichiki, Y. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The dolphin kick movement is commonly used in swimming. The low back pain (LBP) while using the dolphin kick motion is complained by many swimmers and that greatly influences their performance. Cailliet (1968) stated that LBP is caused by kinematic problems in the lumbar, the hip joint and the pelvis. Thus, the kinematic analysis that was included includes the pelvis, the hip joint as well as the lumber vertebrae was necessary for the prevention of the LBP. However, underwater analysis of the dolphin kick was not enough to explain the injury mechanism. Therefore the purpose of this study was the kinematic analysis of the lumbar, the lumbosacral, and the hip joints in the dolphin kick. These results suggest the strong stress was applied at lumbosacral part. Kanaoka et al. (2007) reported the intervertebral disk degeneration at L5-S1 occurred twice as much as at L4-L5 in swimmers. This result agreed with the current study. But, the stress which cause LBP may be difficult to speak only by kinematic analysis. Consequently, furtherbiomechanics studies are needed in swimmers. The dolphin kick was analyzed from the kinematic viewpoint at the lumbar, the pelvic, and hip joint motion in this study. The motion of the hip joint was bigger than the lumbar motion at the trunk flexion. The motion of the hip joint and the lumbosacral joint were bigger than the lumbar motion at the trunk extension.